Asset Governance Strategy, Asset Utilization Optimization, and PNBP Enhancement In PTN-BLU - Agus Santosa; Gita Astyka Rahmanda; Aditya Kurniawardana (International Journal of Management and Business Economics, 2026)
The main objective of this study is to examine the effect of asset governance strategy on asset utilization optimization and non-tax state revenue (PNBP) in Public Service Agency State Universities (PTN BLU), with supervision and control as a mediating variable. Asset governance strategy in this study consists of three main dimensions: asset inventory, legal audit, and asset valuation. A causal quantitative approach was adopted using Structural Equation Modeling (SEM) through the LISREL program. The study involved 275 respondents from 55 PTN BLU. The findings indicate that asset inventory, legal audit, and asset valuation significantly affect supervision and control (t-values > 3.7). Asset inventory has a direct effect on asset utilization optimization (t = 10.13), while legal audit and valuation influence it indirectly through supervision. This confirms that supervision and control serve as an important mediating mechanism in strengthening the relationship between asset governance strategy and asset utilization optimization. Supervision has a significant direct effect on optimization (t = 4.99), and optimization significantly drives PNBP (t = 7.92). The model demonstrated good fit indices (CFI = 0.97; RMSEA = 0.065). These results underscore the importance of an integrated control system to enhance asset efficiency and non-tax revenue contribution in higher education governance.